OPTIMIZED EXTRACTION AND IMMUNOSTIMULATORY EFFECTS OF POLYSACCHARIDES FROM PSEUDERANTHEMUM PALATIFERUM (NEES) RADLK - Bac, Vo Hoai; Van Anh, Tran Thi; Mai Phuong, Nguyen Thi; Thanh Huong, Nguyen Thi; Truong, Le Van (Vietnam Journal of Biotechnology, 2018)
Pseuderanthemum palatiferum (Ness) Radlk is a tree native of Vietnam with various use in traditional medicine. It has been used for the treatment of many diseases including wound, colitis, stomach-aches, trauma, high blood pressure, nephritis, diarrhoea. However, the research on effective constituents from P. palatiferum has mainly been focused on small-molecular compounds. Some compounds: flavonoids, phytol, palmitic acid, ß-sitosterol, triterpenoid saponin, stigmasterol and salicylic acid have been detected in leaves. Polysaccharides have attracted great attentions for its benefits to human health. Polysaccharides from natural sources have diverse anti-inflammatory, anticoagulant and wound healing activities. In this study, we extracted and determined the polysaccharide content from the leaves of P. palatiferum plant. The polysaccharide content in P. palatiferum leaves was 8.2% (± 0.65) in dry weight. The appropriate polysaccharide extraction conditions were determined as: 25% ethanol, material/solvent ratio (1g/10ml), extracted temperature of 70°C, extraction time 12 hours. The polysaccharide composition was purified by TCA 10%, with a purity of 77.8% (± 1.19). The immunostimulatory activities of polysaccharide XH were also examined in cyclophosphamide (CY)-induced immunosuppressed mice. Mice treated with polysaccharide XH exhibited increased white blood cell counts (p < 0.05) compared with immunosuppressed mice. These results indicate that polysaccharide XH from P. palatiferum can enhance immune function in CY-induced immunosuppressed mice.